Live-cell assays to identify regulators of ER-to-Golgi trafficking - Lisauskas, Tautvydas; Matula, Petr; Claas, Christoph; Reusing, Susanne; Wiemann, Stefan; Erfle, Holger; Lehmann, Lars; Fischer, Peter; Eils, Roland; Rohr, Karl; Starkuviene-Erfle, Vytaute (Traffic, 2012)
We applied fluorescence microscopy-based quantitative assays to living cells to identify regulators of endoplasmic reticulum (ER)-to-Golgi trafficking and/or Golgi complex maintenance. We first validated an automated procedure to identify factors which influence Golgi-to-ER relocalization of GalT-CFP (?1,4-galactosyltransferase I-cyan fluorescent protein) after brefeldin A (BFA) addition and/or wash-out. We then tested 14 proteins that localize to the ER and/or Golgi complex when overexpressed for a role in ER-to-Golgi trafficking. Nine of them interfered with the rate of BFA-induced redistribution of GalT-CFP from the Golgi complex to the ER, six of them interfered with GalT-CFP redistribution from the ER to a juxtanuclear region (i.e. the Golgi complex) after BFA wash-out and six of them were positive effectors in both assays. Notably, our live-cell approach captures regulator function in ER-to-Golgi trafficking, which was missed in previous fixed cell assays, as well as assigns putative roles for other less characterized proteins. Moreover, we show that our assays can be extended to RNAi and chemical screens.